2019
DOI: 10.48550/arxiv.1901.04214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reducing measles risk in Turkey through social integration of Syrian refugees

Abstract: Turkey hosts almost 3.5M refugees and has to face a humanitarian emergency of unprecedented levels. We use mobile phone data to map the mobility patterns of both Turkish and Syrian refugees, and use these patterns to build data-driven computational models for quantifying the risk of epidemics spreading for measles -a disease having a satisfactory immunization coverage in Turkey but not in Syria, due to the recent civil war -while accounting for hypothetical policies to integrate the refugees with the Turkish p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…While numerous studies have demonstrated the value of leveraging telecom data in a variety of applications, reaching operation level is not near [10]. Those studies show the potential of telecom data in various domains, such as urban planning [11], pandemic monitoring of infectious diseases [12][13][14][15][16][17], human dynamics studies [18][19][20][21][22][23][24][25], socio-economic analysis [26][27][28], and disaster risk management [29][30][31]. In the context of traffic, studies have been focused on the assessment of traffic composition [32], travel speed and time duration [33], the number of passengers [34], origin-destination matrices [35][36][37], route choice [38,39], and mode of transport [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have demonstrated the value of leveraging telecom data in a variety of applications, reaching operation level is not near [10]. Those studies show the potential of telecom data in various domains, such as urban planning [11], pandemic monitoring of infectious diseases [12][13][14][15][16][17], human dynamics studies [18][19][20][21][22][23][24][25], socio-economic analysis [26][27][28], and disaster risk management [29][30][31]. In the context of traffic, studies have been focused on the assessment of traffic composition [32], travel speed and time duration [33], the number of passengers [34], origin-destination matrices [35][36][37], route choice [38,39], and mode of transport [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, epidemic models based on metapopulations have been continuously refined to bridge this gap between theory and agent-based simulations. Thus, early models considering agents as random walkers [23][24][25][26] have been improved to include more realistic situations such as the recurrent nature of human mobility [27][28][29][30][31][32] or the coexistence of dierent mobility patterns [33,34] within a population. In particular, recently we proposed a framework called MIR (movement-interaction-return) model [35] which allows the use of real data about the population distribution as well as their recurrent mobility patterns, enabling the assessment of the impact of daily movements on the spread of diseases across a given city.…”
Section: Introductionmentioning
confidence: 99%